2017
DOI: 10.4018/ijgcms.2017040101
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Mental Skills Among Competitive League of Legend Players

Abstract: ESports, also known as competitive video gaming, has seen tremendous growth over the past few years. Several studies have been conducted that examined the potential cognitive benefits of playing video games, but few have examined the psychosocial factors needed to perform at the highest level of competitive video gaming. In this study, the researchers aimed to identify specific mental obstacles players face and any mental techniques gamers already utilize by conducting a qualitative content analysis. Interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 27 publications
1
82
0
11
Order By: Relevance
“…In this context, the focus on gaming addiction has increased [17][18][19], with the inclusion of internet gaming disorder in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) in 2015 [20] and gaming disorder in the International Classification of Diseases and Related Health Problems (ICD-11) in 2018 [21]. In addition, the first studies on eSports performance have emerged, focusing mainly on the cognitive skills and challenges eSports players face [22][23][24]. In terms of research on health and health behavior, however, further research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the focus on gaming addiction has increased [17][18][19], with the inclusion of internet gaming disorder in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) in 2015 [20] and gaming disorder in the International Classification of Diseases and Related Health Problems (ICD-11) in 2018 [21]. In addition, the first studies on eSports performance have emerged, focusing mainly on the cognitive skills and challenges eSports players face [22][23][24]. In terms of research on health and health behavior, however, further research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…On a psychological level, it has been suggested that the competitive and cooperative nature of esports requires similar mental skills as traditional sports (Murphy, 2009;Campbell et al, 2018). Supporting this idea, Himmelstein et al (2017) qualitatively examined the mental skills and obstacles encountered by five League of Legends (LoL) athletes. To achieve optimal performance, 11 mental skills were identified (e.g., staying in the moment, utilizing preperformance routines, adapting to competition).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve optimal performance, 11 mental skills were identified (e.g., staying in the moment, utilizing preperformance routines, adapting to competition). Himmelstein et al (2017) also identified four ways esports athletes acquired their skills (i.e., setting goals, analyzing performance, practicing individual skill, and maintaining a growth mindset). Smith et al (2019), through interviews, investigated the stressors experienced and the associated coping strategies used by seven professional esports competitors.…”
Section: Introductionmentioning
confidence: 99%
“…To keep in mind, the respective skill set varies depending on the characteristics of the played video game. To properly recall these cognitive skills and to achieve optimal performance, eSports athletes also need a strong foundation of mental and psychological skills (e.g., emotional regulation and attentional control) (Himmelstein et al, 2017).…”
Section: Esports-specific Performance Requirementsmentioning
confidence: 99%